Олень пятнистый в Черноморском заповеднике - Берестенников, Д.С. (Вестник зоологии, 1968)
20 head (10 and 10 Cervus nippon hortulorum Sminhoe were delivered to Solenoozerny part of the Black Sea reservation from Askaniya-Nova Zoo in 1957. By 1967 there were already up to 200 head in this part. Individual groups of deer were met in the neighbouring parts 18-25 km far from the Solenoozerny reservation. The favourable conditions of inhabitance told positively not only on the increase of a number of deer, but also on their general development. The article deals with the characteristics of the 'conditions of their inhabitance, reproduction, development, morphological peculiaritie S. A comparison is made of the populations from the Black Sea reservation with the initial one from Primorye Territory and a list of the food plants eaten by the deer in the reservation is presented.